Consumer identity and the sustainable market : the greenwashing effect across multi-brand consumption - Alves, Joana Gonçalves de Azevedo (2021)
Slowly but surely, consumer's imperatively green markets shape the marketing agenda progressively. The requirement of environmental concerns led to developments in approaches to launching a sustainable offering, either driven by companies wanting a contribution to environmental issues and green identity pursuing or by companies which befriend the need of keeping up with their market share. Nonetheless, apart from taking an interest in sustainable living, brands started to use its parent-brand to enter new categories and markets: brand extensions. This strategy has not only the goal of increasing awareness for the brand name but also enhancing profitability from offerings in more than one product category. As a purpose, this paper approaches how consumer identity influences consumer considerations regarding green scales of green contribution according to their environmental fit perceptions, comparing from the greenwashing impact of a whole parent brand to only a brand extension. To a better evaluation, it was elaborated a survey concerning brand and brand extension within purpose-driven brands that advocate sustainability and the brands that repudiate the greenwashing effect. Through the understanding of data manipulation, the goal is to comprehend, within the factors that affect green brand perception, at which extend consumer identity influences the decision on grading both parent brand and brand extensions as well as at what measure this happens.